Coordinated unsaturated alumina material as well as preparation method and application thereof
By introducing coordination unsaturated structures and porous structures into the alumina materials, the problems of poor selectivity and low adsorption capacity of existing alumina materials in depth removal are solved, and efficient fluorine ion adsorption and fluorine removal are achieved.
Patent Information
- Application Number
- CN202411899536.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing alumina adsorbent materials have problems such as poor selectivity and low adsorption capacity in deep fluorine removal.
Coordinated unsaturated alumina material was prepared by adding glacial acetic acid and urea to a solution containing an aluminum salt, performing hydrothermal reaction and performing heat treatment. The material selectively adsorbs fluorine through chemical coordination and provides high capacity adsorption sites through the porous structure.
High selectivity and high capacity fluorine ion adsorption is achieved, which significantly improves the fluorine removal efficiency and is suitable for treating low-concentration fluorine-containing wastewater.
Smart Images

Figure CN119706895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluorine-containing wastewater treatment, and in particular to a coordination unsaturated aluminum oxide material and a preparation method and application thereof. Background Art
[0002] Fluorine-containing chemical raw materials are widely used in electronics, photovoltaics, high-speed rail, chemical industry and other industries. With the widespread use of fluorine-containing chemical raw materials, a large amount of fluorine-containing wastewater is generated. After the fluorine-containing wastewater is discharged into natural water bodies, the concentration of fluoride in the water body will increase, affecting the water quality. High concentrations of fluoride will also inhibit the growth of aquatic organisms and destroy the balance of the aquatic ecosystem. Therefore, the removal of fluoride in wastewater is an important environmental protection issue currently faced.
[0003] Precipitation is a common method for removing fluoride from wastewater. Among them, one precipitation method can recover fluorite or cryolite from wastewater and is widely used to treat high-concentration fluoride-containing wastewater, but is not suitable for low-concentration fluoride-containing wastewater. Another precipitation method is to add aluminum salts to the wastewater to achieve deep fluoride removal through coordination and electrostatic effects, but this method may be "pseudo" fluoride removal, and exchangeable and non-exchangeable fluoride is difficult to remove. In addition, the fluoride removal rate of this method is not high. Therefore, the development of deep fluoride removal technology is imminent.
[0004] Compared with the precipitation method, the adsorption method has the advantages of simple operation, wide applicability, and stable operation. It has great application prospects in deep fluoride removal. Currently, commonly used adsorbents include activated carbon, alumina, and natural materials (zeolite, kaolin, etc.). Among them, activated alumina adsorption is the most mature method for deep treatment of fluoride-containing wastewater, but there are still problems such as poor fluoride adsorption selectivity and low adsorption capacity. Summary of the invention
[0005] The main purpose of the present invention is to provide a coordinated unsaturated alumina adsorption material, aiming to solve the technical problems of poor selectivity and low adsorption capacity of the above-mentioned existing adsorption materials.
[0006] In a first aspect, the present invention provides a method for preparing a coordination unsaturated alumina material, comprising the following steps:
[0007] In a solution containing an aluminum salt, glacial acetic acid is added, followed by urea, and a hydrothermal reaction is performed to obtain a solid product;
[0008] The solid product is heat-treated at 200-600° C. to obtain the coordinated unsaturated alumina material.
[0009] Furthermore, the molar ratio of the aluminum salt to the glacial acetic acid is 1:0.5-5.
[0010] Furthermore, the molar ratio of the aluminum salt to urea is 1:0.1-2.
[0011] Furthermore, the hydrothermal reaction satisfies the following conditions: the reaction temperature is 80°C to 240°C, and the reaction time is 2h to 8h.
[0012] Furthermore, the heat treatment includes the following process: heating to 200-600°C at a heating rate of 1-5°C / min, and keeping the temperature for 30-180min.
[0013] Furthermore, in the solution containing aluminum salt, the aluminum salt includes at least one of aluminum sulfate, aluminum nitrate, and aluminum chloride; and the solvent is an organic solvent.
[0014] Furthermore, the organic solvent is isopropanol or ethylene glycol.
[0015] In a second aspect, the present invention provides a coordination unsaturated alumina material prepared by the preparation method described in the first aspect.
[0016] In a third aspect, the present invention provides a method for removing fluorine, comprising the following steps: adding the coordination unsaturated alumina material of the second aspect to fluorine-containing wastewater, stirring the wastewater, and removing fluoride ions from the fluorine-containing wastewater.
[0017] Furthermore, the fluoride ion concentration in the fluoride-containing wastewater is n, and n satisfies: 0 mg / L <n≤100 mg / L。
[0018] The preparation method provided by the present invention can be used to prepare the unsaturated , , At least one of the above is introduced into the alumina material, and functional groups such as hydroxyl and carbonyl are introduced on its surface, so as to finally obtain a coordinated unsaturated alumina material with good selectivity, high adsorption capacity and porous morphology.
[0019] The coordinated unsaturated alumina material provided by the present invention can selectively adsorb fluorine by utilizing chemical coordination, and its porous structure can provide a large number of adsorption sites, thereby achieving high-capacity adsorption of fluorine. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0021] Figure 1 The microscopic characterization diagram of the aluminum oxide material of Example 1 and Comparative Example 1,
[0022] In the figure, a is a microscopic characterization diagram of the aluminum oxide material of Example 1, and b is a microscopic characterization diagram of the aluminum oxide material of Example 1. Figure 1 Microscopic characterization of the aluminum oxide material of Comparative Example 1;
[0023] Figure 2 The infrared spectra of the aluminum oxide materials of Example 1 and Comparative Example 1;
[0024] Figure 3 This is a bar chart comparing the defluorination effects of the alumina materials of Example 1 and Comparative Example 1 in Test Example 1;
[0025] Figure 4 This is a bar graph comparing the defluorination effects of the aluminum oxide material of Example 1 in Test Example 2 on solutions with different fluorine concentrations. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0027] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0028] In this application, the term "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0029] In this application, the terms "first" and "second" are used only for descriptive purposes to distinguish purposes such as substances from each other, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0030] In this application, references to "one embodiment", "an example", or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment, embodiment, or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment", "an embodiment", "an example", or "an example" appearing in various places throughout the specification do not necessarily refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination.
[0031] In response to the problems of poor selectivity and low adsorption capacity of fluorine in activated alumina, researchers have improved the fluorine removal ability of activated alumina to a certain extent by introducing other substances (lanthanum, graphene, hydroxyapatite, etc.) to modify the surface of alumina. However, due to the complexity of the surface modification preparation process and the expensive materials such as lanthanum used in the modification, this has increased the cost of fluorine removal from alumina to a certain extent.
[0032] In view of this, it is necessary to provide a high-efficiency and low-cost alumina adsorption material to solve or at least alleviate the above-mentioned defects of the existing alumina materials such as poor fluorine removal selectivity and low capacity.
[0033] In a first aspect, the present invention provides a method for preparing a coordination unsaturated alumina material, comprising the following steps:
[0034] In a solution containing an aluminum salt, glacial acetic acid is added, followed by urea, and a hydrothermal reaction is performed to obtain a solid product;
[0035] The solid product is heat-treated at 200-600° C. to obtain the coordinated unsaturated alumina material.
[0036] In the present invention, aluminum salt and glacial acetic acid can react to obtain aluminum acetate, and then urea is added to obtain partial aluminum urea and aluminum oxide particles. Aluminum acetate decomposes under heat treatment and generates aluminum oxide during the decomposition process. The temperature of the heat treatment affects the degree of decomposition, thereby retaining some groups (such as hydroxyl, carboxyl, etc.) on the surface of the material. At the same time, aluminum urea and aluminum acetate will produce carbon dioxide, ammonia and other gases during the decomposition process, which is conducive to the formation of a porous structure. At the same time, a suitable heat treatment temperature is also conducive to , , The formation of unsaturated aluminum species.
[0037] Illustratively, the temperature of the heat treatment is any one of 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, etc., or a range consisting of any two of them.
[0038] The aluminum salt is not particularly limited in the present invention, and may be, for example, aluminum chloride, aluminum nitrate, aluminum sulfate, or the like.
[0039] In an optional embodiment, the molar ratio of the aluminum salt to the glacial acetic acid is 1:0.5~5.
[0040] Illustratively, the molar ratio of the aluminum salt to the glacial acetic acid is 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.
[0041] In an optional embodiment, the molar ratio of the aluminum salt to urea is 1:0.1-2.
[0042] Among them, urea decomposes under hydrothermal conditions to produce ammonia, gradually increasing the pH value of the system. Therefore, the molar ratio of aluminum salt to urea determines the rate of change of pH value and the final pH level, which affects the hydrolysis of aluminum and the formation of alumina, thereby affecting the specific surface area and pore structure of alumina. The ratio as mentioned above may lead to a higher specific surface area and a more developed pore structure, which is beneficial for fluorine adsorption applications.
[0043] Coordinated unsaturated alumina materials usually require a high specific surface area, and a suitable hydrothermal temperature can ensure the size of its grains, thereby ensuring the specific surface area of the coordinated unsaturated alumina material. Therefore, it is key to control the hydrothermal reaction to maintain an appropriate grain size; in addition, the hydrothermal temperature also affects the pore structure of the coordinated unsaturated alumina material, including the pore size and pore volume. The appropriate temperature can promote the formation of the pore structure, which is beneficial to its application in adsorption. Therefore, in an optional embodiment, the hydrothermal reaction meets the following conditions: the reaction temperature is 80°C~240°C, and the reaction time is 2h~8h.
[0044] Exemplarily, the temperature of the hydrothermal reaction is any value among 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, etc., or a range consisting of any two of them, and the reaction time of the hydrothermal reaction is any value among 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc., or a range consisting of any two of them.
[0045] The parameters of the heat treatment affect the specific surface area of alumina. Generally speaking, heat treatment with a higher heating rate will lead to rapid grain growth and a decrease in specific surface area. Moreover, the heating program and holding time of the heat treatment will affect the pore size, pore volume and pore distribution of the alumina material. Therefore, selecting appropriate heat treatment parameters to maintain a high specific surface area is relatively important for adsorption applications. In an optional embodiment, the process includes the following: heating to 200~600°C at a heating rate of 1~5°C / min and keeping warm for 30~180 minutes.
[0046] Among them, the heat treatment process as described above can regulate parameters such as the specific surface area, pore size, pore volume and pore distribution of the alumina material, thereby further improving the adsorption of the alumina material.
[0047] In an optional embodiment, in the solution containing aluminum salt, the aluminum salt includes at least one of aluminum sulfate, aluminum nitrate, and aluminum chloride; and the solvent is an organic solvent.
[0048] In an optional embodiment, the organic solvent is isopropanol or ethylene glycol.
[0049] In a second aspect, the present invention provides a coordination unsaturated alumina material prepared by the preparation method described in the first aspect.
[0050] In a third aspect, the present invention provides a method for removing fluorine, comprising the following steps: adding the coordination unsaturated alumina material of the second aspect to fluorine-containing wastewater, stirring the wastewater, and removing fluoride ions from the fluorine-containing wastewater.
[0051] In an optional embodiment, the fluoride ion concentration in the fluoride-containing wastewater is n, and n satisfies: 0 mg / L <n≤100mg / L。
[0052] In some embodiments, the fluoride ion concentration in the fluoride-containing wastewater is n, and n satisfies: 1.5 mg / L <n≤100 mg / L。
[0053] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Unless otherwise specified, the reagents involved in the embodiments of the present invention are all commercially available products and can be purchased through commercial channels.
[0055] Example 1
[0056] This example provides a coordination unsaturated aluminum oxide material, and the preparation method thereof comprises the following steps:
[0057] Dissolve 50 mmol aluminum sulfate in 50 mL ethylene glycol, add 5 mL (87 mmol) of glacial acetic acid dropwise under stirring, then add 20 mmol urea and stir evenly, transfer the solution into a polytetrafluoroethylene liner, perform hydrothermal reaction at 180°C for 4 hours, cool and wash with ethanol and ultrapure water for 3 to 5 times respectively to obtain a white powder;
[0058] The white powder was placed in a quartz boat in a tube furnace, and the temperature was raised to 400°C at a heating rate of 2°C / min, kept at that temperature for 60 minutes, and then cooled to room temperature at a cooling rate of 2°C / min to obtain sample 1.
[0059] The microscopic characterization of sample 1 is as follows Figure 1 As shown in a, Figure 1 It can be seen that there is a porous structure on the surface of sample 1;
[0060] The infrared spectrum of sample 1 is as follows Figure 2 As shown by Figure 2 It can be seen that the surface of sample 1 contains hydroxyl groups, carboxyl groups and unsaturated aluminum.
[0061] Example 2
[0062] This example provides a coordination unsaturated aluminum oxide material, and the preparation method thereof comprises the following steps:
[0063] Dissolve 50 mmol aluminum sulfate in 50 mL ethylene glycol, add 5 mL (87 mmol) of glacial acetic acid dropwise under stirring, then add 5 mmol urea and stir evenly, transfer the solution into a polytetrafluoroethylene liner, perform hydrothermal reaction at 180°C for 4 hours, cool, and wash with ethanol and ultrapure water for 3 to 5 times respectively to obtain a white powder;
[0064] The white powder was placed in a quartz boat in a tube furnace, the temperature was raised to 400°C at a heating rate of 2°C / min, kept at that temperature for 60 minutes, and then cooled to room temperature at a cooling rate of 2°C / min to obtain sample 1-1.
[0065] Example 3
[0066] This example provides a coordination unsaturated aluminum oxide material, and the preparation method thereof comprises the following steps:
[0067] Dissolve 50 mmol of aluminum sulfate in 50 mL of ethylene glycol, add 5 mL (87 mmol) of glacial acetic acid dropwise under stirring, then add 100 mmol of urea and stir evenly, transfer the solution into a polytetrafluoroethylene liner, perform hydrothermal reaction at 180°C for 4 hours, cool, and wash with ethanol and ultrapure water for 3 to 5 times respectively to obtain a white powder;
[0068] The white powder was placed in a quartz boat in a tube furnace, the temperature was raised to 400°C at a heating rate of 2°C / min, kept at that temperature for 60 minutes, and then cooled to room temperature at a cooling rate of 2°C / min to obtain sample 1-2.
[0069] Example 4
[0070] This example provides a coordination unsaturated aluminum oxide material, and the preparation method thereof comprises the following steps:
[0071] Dissolve 50 mmol aluminum sulfate in 50 mL ethylene glycol, add 5 mL (87 mmol) of glacial acetic acid dropwise under stirring, then add 20 mmol urea and stir evenly, transfer the solution into a polytetrafluoroethylene liner, perform hydrothermal reaction at 100 °C for 5 h, cool and wash with ethanol and ultrapure water for 3 to 5 times respectively to obtain a white powder;
[0072] The white powder was placed in a quartz boat in a tube furnace, and the temperature was raised to 400°C at a heating rate of 2°C / min, kept at that temperature for 60 minutes, and then cooled to room temperature at a cooling rate of 2°C / min to obtain samples 1-3.
[0073] Example 5
[0074] This example provides a coordination unsaturated aluminum oxide material, and the preparation method thereof comprises the following steps:
[0075] Dissolve 50 mmol aluminum sulfate in 50 mL ethylene glycol, add 5 mL (87 mmol) of glacial acetic acid dropwise under stirring, then add 20 mmol urea and stir evenly, transfer the solution into a polytetrafluoroethylene liner, perform hydrothermal reaction at 180°C for 4 hours, cool and wash with ethanol and ultrapure water for 3 to 5 times respectively to obtain a white powder;
[0076] The white powder was placed in a quartz boat in a tube furnace, heated to 250°C at a heating rate of 2°C / min, kept at that temperature for 100 min, and then cooled to room temperature at a cooling rate of 2°C / min to obtain samples 1-4.
[0077] Comparative Example 1
[0078] Commercially purchased nano-alumina particles were used as a comparison and named Sample 2.
[0079] The microscopic characterization of sample 2 is as follows Figure 1 As shown in b, Figure 1 It can be seen that there is no porous structure on the surface of sample 2;
[0080] The infrared spectrum of sample 2 is as follows Figure 2 As shown by Figure 2It can be seen that the surface of sample 1 does not contain hydroxyl groups, carboxyl groups and unsaturated aluminum.
[0081] Test Example 1
[0082] The removal rate of fluorine by the coordination unsaturated alumina materials of the above embodiments and comparative examples was tested. The testing method comprises the following steps:
[0083] The simulated fluoride-containing wastewater prepared with sodium fluoride and sodium sulfate was used, where the fluoride ion concentration was 20 mg / L and the sulfate concentration was 100 mg / L; multiple 150 mL beakers were used, 100 mL of fluoride-containing wastewater was added respectively, and then different coordinated unsaturated alumina materials were added respectively, where the amount of coordinated unsaturated alumina materials added was 0.5 g / L, and the reaction was carried out at a stirring rate of 300 rpm for 30 minutes. The samples were filtered with a 0.45 μm filter head, and the fluoride ion concentration in the solution was tested using a fluoride ion electrode. The experimental results of sample 1 and sample 2 are shown in Figure 1. Figure 3 As shown by Figure 3 It can be seen that after 30 minutes of reaction, the fluorine removal rates of sample 1 and sample 2 are 89.6% and 33.3% respectively.
[0084] Furthermore, the fluorine removal rate of sample 1-1 is 80.2%, the fluorine removal rate of sample 1-2 is 73.4%, the fluorine removal rate of sample 1-3 is 85.4%, and the fluorine removal rate of sample 1-4 is 82.6%.
[0085] Test Example 2
[0086] The selective removal of fluorine by the coordination unsaturated alumina materials of the above embodiments and comparative examples was tested. The testing method comprises the following steps:
[0087] 1) Test the interference of chloride ions: Sodium chloride, sodium fluoride and water were mixed to make the prepared mixture contain 100 mg / L chloride ions and 20 mg / L fluoride ions. Equal amounts of the above mixture were added to multiple 150 mL beakers, and then different samples were added. The sample input amount was 0.5 g / L. The reaction was carried out at a stirring rate of 300 rpm for 30 min. The samples were filtered with a 0.45 μm filter head, and the fluoride ion concentration in the solution was tested using a fluoride ion electrode;
[0088] Test results: The fluorine removal rate of sample 1 reached 92.1%; the fluorine removal rate of sample 2 was 40.2%.
[0089] 2) Test the interference of nitrate ion: Sodium nitrate, sodium fluoride and water were mixed to make the prepared mixed solution contain 100 mg / L nitrate ion and 20 mg / L fluoride ion. Equal amounts of the mixed solution were added to multiple 150 mL beakers, and then different samples were added. The sample input amount was 0.5 g / L. The reaction was carried out at a stirring rate of 300 rpm for 30 min. The sample was filtered with a 0.45 μm filter head, and the fluoride ion concentration in the solution was tested using a fluoride ion electrode.
[0090] Test results: The fluorine removal rate of sample 1 reached 87.5%; the fluorine removal rate of sample 2 was 36.4%.
[0091] 3) Test the interference of sulfate, nitrate and copper ions: Sodium sulfate, sodium nitrate, sodium fluoride, copper sulfate pentahydrate and water were mixed to make the prepared mixture contain 100 mg / L sulfate ions, 125 mg / L nitrate, 10 mg / L copper ions and 20 mg / L fluoride ions. Equal amounts of the above mixtures were added to multiple 150 mL beakers, and then different samples were added. The sample input amount was 0.5 g / L. The reaction was carried out at a stirring rate of 300 rpm for 30 min. The samples were filtered with a 0.45 μm filter head, and the fluoride ion concentration in the solution was tested using a fluoride ion electrode.
[0092] Test results: The fluorine removal rate of sample 1 reached 88.5%; the fluorine removal rate of sample 2 was 21.6.4%.
[0093] Test Example 3
[0094] The fluorine removal rate of the coordinated unsaturated alumina material of Example 1 above for solutions with different fluorine contents is tested, and the testing method comprises the following steps:
[0095] The simulated fluoride-containing wastewater prepared with sodium fluoride and sodium sulfate was used, in which the fluoride ion concentration gradient was 10, 20, and 30 mg / L, and the sulfate concentration was 100 mg / L; three 150 mL beakers were used, 100 mL of fluoride-containing wastewater was added respectively, and then 0.5 g / L of sample 1 was added respectively, and the reaction was carried out at a stirring rate of 300 rpm for 30 min. The sample was filtered with a 0.45 μm filter head, and the fluoride ion concentration in the solution was tested using a fluoride ion electrode.
[0096] The experimental results are as follows Figure 4 As shown, after 30 minutes of reaction, the fluoride ion concentrations in the three beakers were 10, 20, and 30 mg / L. Calculation showed that the fluoride removal rates in the wastewater were 89.6%, 89.8%, and 86.4%, respectively.
[0097] Summary: Based on the above tests, Figure 1 and Figure 2It can be seen that traditional alumina is a nanoparticle, has no porous structure, has few adsorption sites, and has a much lower adsorption capacity for fluoride ions than the coordination unsaturated alumina material of the present invention. Secondly, the selectivity of traditional nano alumina particles for adsorbing fluoride ions is also poor.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a coordination unsaturated alumina material, characterized in that: The following steps are involved: In a solution containing an aluminum salt, glacial acetic acid is added, followed by urea, and a hydrothermal reaction is performed to obtain a solid product; The solid product is heat-treated at 200-600° C. to obtain the coordinated unsaturated alumina material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the aluminum salt to the glacial acetic acid is 1:0.5-5.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the aluminum salt to urea is 1:0.1-2.
4. The preparation method according to claim 1 or 2, characterized in that: The hydrothermal reaction satisfies the following conditions: the reaction temperature is 80°C to 240°C, and the reaction time is 2h to 8h.
5. The preparation method according to claim 1 or 2, characterized in that: The heat treatment comprises the following process: heating to 200-600° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 30-180 min.
6. The preparation method according to claim 1 or 2, characterized in that: In the solution containing aluminum salt, the aluminum salt includes at least one of aluminum sulfate, aluminum nitrate, and aluminum chloride, and the solvent is an organic solvent.
7. The preparation method according to claim 6, characterized in that: The organic solvent is isopropanol or ethylene glycol.
8. A coordination unsaturated alumina material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. A method for removing fluorine, characterized in that: The method comprises the following steps: adding the coordinated unsaturated alumina material of claim 8 into fluorine-containing wastewater, stirring the wastewater, and removing fluorine ions from the wastewater.
10. The method according to claim 9, characterized in that The fluoride ion concentration in the fluoride-containing wastewater is n, and n satisfies: 0 mg / L <n≤100 mg / L。
Citation Information
Patent Citations
Preparation method and application of flaky aluminum oxide having porous structure
CN107128961A
Urea glue adsorption material for defluorination, and preparation method thereof
CN113856648A
Cited By
Method for preparing aluminum-based anode mud and sodium alginate composite microspheres and adsorbing trace fluorine
CN122141616A